IMPROVING STUDENTS’ READING COMPREHENSION THROUGH SMALL GROUP WORK TECHNIQUE AT THE SEVENTH GRADE STUDENTS OF SMP ROSA JAYA - A.Tajdi Amal Faozi; Irma Savitri Sadikin (IKIP Siliwangi, 2018)
The objective of this research entitled Improving Students’ Reading Comprehension through Small Group Work Technique at the Seventh Grade Students of SMP ROSA JAYA on academic year 2016/2017 was to find out whether or not the technique was effective to improve the students’ reading comprehension. In this research, the method that the writer used was one group pretest-posttest design and quantitative research method. The instruments of the research were pretest and posttest which contained five questions which should be answered based on a text they read. The pretest was given to find out the comprehension of the students at the beginning before the treatment, and the posttest was given to find out the ability of the students after they were given treatment. The research population was the students of the seventh grade of SMP ROSA JAYA which consisted of three classrooms, and the sample of the research was 30 students selected using random sampling technique. The data of this research were collected by giving the students pretest and posttest. The collected data were analyzed by using t-test formula. The result of this research showed that: the mean score of pretest was 59.67. The mean score of posttest was 77.83. The t-observed was 4.812. The t-table critical value was 29 and significance level at 0.05 was 2.045. Based on the data analysis, the writer concluded that the alternative hypothesis was accepted because the tobs was higher than the ttable (4.812 > 2.045). It also meant that Improving Students’ Reading Comprehension Through Small Group Work Technique at the Seventh Grade Students of SMP ROSA JAYA on Academic Year 2016/2017 has significantly shown that the technique could improve the students’ reading comprehension.